Global mean nitrogen recovery efficiency in croplands can be enhanced by optimal nutrient, crop and soil management practices - Luncheng You; Gerard H. Ros; Yongliang Chen; Qi Shao; Madaline D. Young; Fusuo Zhang; Wim de Vries (Nature Communications)
Abstract An increase in nitrogen (N) recovery efficiency, also denoted as N use efficiency (NUEr), is crucial to reconcile food production and environmental health. This study assessed the effects of nutrient, crop and soil management on NUEr accounting for its dependency on site conditions, including mean annual temperature and precipitation, soil organic carbon, clay and pH, by meta-regression models using 2436 pairs of observations from 407 primary studies. Nutrient management increased NUEr by 3.6-11%, crop management by 4.4–8%, while reduction in tillage had no significant impact. Site conditions strongly affected management induced changes in NUEr, highlighting their relevance for site-specific practices. Data driven models showed that the global mean NUEr can increase by 30%, from the current average of 48% to 78%, using optimal combinations of nutrient (27%), crop (6.6%) and soil (0.6%) management. This increase will in most cases allow to reconcile crop production with acceptable N losses to water. The predicted increase in NUEr was below average in most high-income regions but above average in middle-income regions.